The role of fatty acids on endoplasmic reticulum proteostasis in non-alcoholic fatty liver disease - Estrada, Andrea Lee, author; Pagliassotti, Michael, advisor; Miller, Benjamin, committee member; Foster, Michelle, committee member; Frye, Melinda, committee member; Gentile, Christopher, committee member (Colorado State University. Libraries, 2017)
Non-alcoholic fatty liver disease (NAFLD) is currently a significant health concern in both adults and children. NAFLD is a disease characterized by accumulation of fat in the liver (steatosis) in the absence of chronic alcohol consumption. In some individuals, steatosis progresses to non-alcoholic steatohepatitis (NASH), which is characterized by steatosis, inflammation, apoptosis and fibrosis, and can ultimately lead to end-stage liver disease. The underlying causes of NAFLD are unclear, although recent evidence has implicated the endoplasmic reticulum (ER) in both the development of steatosis and progression to NASH. Disruption of ER homeostasis or "ER stress" has been observed in the livers and adipose tissue of humans with NAFLD and/or obesity. Downstream signaling events that arise from ER stress include lipid biogenesis, insulin resistance, inflammation, fibrosis and apoptosis, all of which are hallmark features of NAFLD and NASH. Elevated circulating free fatty acids are a characteristic feature of humans with NAFLD and are positively correlated with disease severity. Our laboratory has demonstrated that in rodents, selective elevation of circulating free fatty acids induces ER stress in liver and adipose tissue. In addition, ER stress is exacerbated when the composition of fatty acids includes levels of saturated fats comparable to what is encountered in the typical western diet. We, and others, have also demonstrated that saturated fatty acids provoke ER stress in cultured hepatocytes, pancreatic beta cells, and various other cell types. These data have led to the hypothesis that the composition of fatty acids presented to and stored within the liver is an important determinant of ER homeostasis. ER stress is characterized by an accumulation of unfolded proteins within the lumen of the ER. Therefore, the presence of ER stress in NAFLD implies that there is an imbalance between the protein load presented to the ER, and the ability of the ER to process, degrade and/or remove these proteins. The overall aim of this thesis was to examine how saturated fatty acids disrupt ER homeostasis in the liver. We explored in vivo hepatic protein synthesis in response to acute dietary intervention, namely using diets high saturated fat and sucrose, which promote hepatic steatosis and insulin resistance in rats. We utilized the saturated fat, palmitate in controlled delivery to H4IIE liver hepatocytes in order to assess protein synthesis and components of protein degradation. Lastly, we examined the roles of calcium homeostasis and protein palmitoylation in response to palmitate treatment in H4IIE liver hepatocytes. We found that diets high in saturated fat did not affect hepatic protein synthesis in rats. In agreement with this observation, H4IIE hepatocyte treatment with palmitate did not selectively stimulate cellular protein synthesis. Provision of palmitate increased protein ubiquitination, this result was observed independent of proteasome activity or total cellular protein degradation. Lastly, we found that palmitate-induced ER stress was characterized by a reduction in sarcoendoplasmic reticulum ATPase (SERCA) activity. Our data suggest that saturated fatty acid-induced ER stress is mediated via reduced SERCA activity, and subsequent disruption in protein handling.